Lower risk factors for better learning. (Research'eu results magazine)
A study has examined the effects of maltreatment and neglect on children's pre-academic skills, as well as the role of 'executive functions' (EFs) as mediators here. This innovative approach can shed light on the relationship between risk and protective factors and the pre-academic and EF skills of at risk-preschoolers.